Type 2 Myocardial Infarction Resulted from the Left Thoracic Stomach - Shi,Yaming (2020)
Abstract The universal definition of myocardial infarction (MI) provides five subtypes of acute myocardial infarction (AMI). We present an interesting case of a type 2 myocardial infarction caused by the dilation of the left thoracic stomach.